Activities of the Armed Forces of Latvia, Lithuania and Estonia: Experience for Ukraine - V. V. Chumak (Bulletin of Kharkiv National University of Internal Affairs)
The current state of activity of the Armed Forces of the Baltic States such as Latvia, Lithuania and Estonia has been studied. The experience of the Armed Forces of these countries in ensuring collective defense, security and peace in accordance with NATO standards has been analyzed.